1998
DOI: 10.2307/4003322
|View full text |Cite
|
Sign up to set email alerts
|

Diet Selection by Sheep and Goats on Mediterranean Heath-Woodland Range

Abstract: The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Aniials grazed a mountain rangeland composed of Quercus ilex woodland and CuUuna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 32 publications
0
66
0
Order By: Relevance
“…The benefit of growing completely protected by shrubs has been shown in the same study area for both other less-palatable tree species, such as Taxus baccata (García et al 2000), as well as for highly palatable species, such as Acer granatense (Hódar et al 1998;Castro 2000). The trophic generalism of the domestic and wild Mediterranean ungulates (e.g., Martínez 1995;García-González and Cuartas 1992b;Fandós 1991;Bartolomé et al 1998 our study sites seem not to benefit from any deterrent property of neighbouring shrubs other than mechanical barriers against the ungulates.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The benefit of growing completely protected by shrubs has been shown in the same study area for both other less-palatable tree species, such as Taxus baccata (García et al 2000), as well as for highly palatable species, such as Acer granatense (Hódar et al 1998;Castro 2000). The trophic generalism of the domestic and wild Mediterranean ungulates (e.g., Martínez 1995;García-González and Cuartas 1992b;Fandós 1991;Bartolomé et al 1998 our study sites seem not to benefit from any deterrent property of neighbouring shrubs other than mechanical barriers against the ungulates.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, mammalian herbivory is extremely frequent in Mediterranean habitats, most being overgrazed and overbrowsed . Finally, the Mediterranean mammalian herbivores are generalists, consuming disparate types of herbs and shrubs (Martínez 1988(Martínez , 1990(Martínez , 1995García-González and Cuartas 1989, 1992a, 1992bFandós 1991;Cuartas and García-González 1992), often resulting in serious damage to Mediterranean woody plants (Cuartas and García-González 1992;Bartolomé et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to Wadhwa et al (2006), cabbage leaves have excellent palatability when fed to goats. The ingestive behaviour of goats, however, differs from that of sheep (Nicol et al, 1987;Bartolome et al, 1998). The ADG of lambs fed the diets containing cabbage was lower (P <0.05) compared with lambs fed the control diet (Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…Although Wadhwa et al (2006) reported good animal performance when cabbage was fed to goats, the performance of young lambs fed diets supplemented with cabbage might differ from that of goats because these small ruminants differ in their grazing behaviour and digestive dynamics (Nicol et al, 1987;Bartolome et al, 1998). In addition, the goats used by Wadhwa et al (2006) were six years old and weighed 62 kg live weight, while sheep feedlot operations in South Africa use weaned lambs that range between 22 and 26 kg live weight.…”
Section: Introductionmentioning
confidence: 99%
“…While this representation highlights the predominance of browse in the diet of goats, a finding reported by many authors (e.g. Squires 1980;Teague 1989;Bartolome et al 1998;Ramirez 1999), the literature also reflects considerable variation on this theme and points to goats as highly selective, or 'fastidious', grazers while willing to accept a wide variety of forages (Devendra and Burns 1983).…”
mentioning
confidence: 71%